PERUBAHAN PARADIGMA PEMBANGUNAN DAERAH DI INDONESIA - Mafruhah, Izza (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2001)
Every development process always demands the chancing of better condition. In 5 Pelita (Development for Five Year Period) of Orde Baru (new period), local government has less proportion that cause some unsatisfaction service in society. Considering to this problem, Indonesian government arranges and discusses a constitution that hopefully will be able to receive aspiration and give wide opportunity to local government to improve and compete with the others.